INTERFACE EQUILIBRATION PROCESSES AND THEIR EFFECTS ON WETTABILITY AND INTERFACIAL ENERGY - (:unkn) unknown (My University, 2009)
Surface/interface equilibration and wettability modification of organic liquids are two important phenomena in many practical applications including subsurface remediation, detergency and food industry. Although surface/interface equilibration and wettability are two different processes, they are closely related to each other when applied to organic liquids. The objective of this research work is to study the dynamics of surface equilibration process of organic liquids and its implication on the change of wettability.

Because of their low aqueous solubilities, dense nonaqueous phase liquids (DNAPLs) persist as long-term sources of contamination. Although natural dissolution can occur slowly, because it occurs at DNAPL-water interfaces, it may influence the wettability of aquifer materials in the presence of DNAPLs. The wettability of aquifer materials and properties of DNAPL-water interfaces can influence how DNAPLs infiltrate through the subsurface, and how easily they can be remediated.

Surfactants are widely used in subsurface remediation, detergency, oil recovery, pharmaceutical industry and food industry. Surfactant monomer adsorbs on the surface or interface. When surfactant adsorbs, surface/interfacial tension initially is not equal to equilibrium interfacial tension of the system. Depending on the fluid types, phase volumes, concentration and interfacial area it may take milliseconds to days to attain equilibrium surface/interfacial tension. So for different practical applications, it is very important to understand the adsorption kinetics of surfactant and the corresponding effect on dynamic surface/interfacial tension over time.

This research work examines the dynamics of surface/interface equilibration of organic liquids and its effect on wettability modification. The study has been accomplished by three different types of experiments: (i) Dissolution of DNAPLs (sessile drop) in water (in presence and absence of surfactant), (ii) Dilution of different types (cationic, anionic and nonionic) of surfactant solution (dilution of surfactant pendent drop in air by injecting water into the drop) and (iii) Evaporation of surfactant solution (pendent drop in air). Considering the experimental result, numerical models have been developed to understand the surface/interface equilibration phenomena and its effect on wettability modification.

The result of this study will provide a better understanding of surface/interface equilibration phenomena of organic liquids and their effects on wettability modification.
Keywords: Surface chemistry; Dense nonaqueous phase liquids; Surface active agents